2019
DOI: 10.1101/746602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of Microbial Beta-Glucuronidase Does Not Prevent Breast Carcinogenesis in the Polyoma Middle T Mouse

Abstract: Purpose: To demonstrate whether inhibition of intestinal microbial beta (b)-glucuronidase (BGUS) abrogates tumor formation in a MMTV-PyMT mouse breast cancer model. Methods: Female MMTV-PyMT heterozygote mice (4 weeks old) were randomized to oral gavage with vehicle or UNC10201652 (20 µg/day), a microbial BGUS inhibitor, for 9 weeks. The entire animal carcass was assessed for tumor deposits by histology and immunohistochemical staining for tumor (Ki67, PCNA) and breast specific (ER, PR, Cyclin D1, aSMA, Integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Recently, Ervin et al [ 44 ] have demonstrated that the administration of fecal samples rich in these enzymatic activities to mice did not correlate with an increase in tumorogenesis, suggesting that the function of these enzymes could be a way of reactivating estrogens that can be further metabolized in different ways (e.g., hydrolyzed, epimerized, oxidized, methylated) in distal sites. In parallel, Beck et al [ 75 ] demonstrated that treatment with β-glucuronidase inhibitors did not prevent breast cancer in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ervin et al [ 44 ] have demonstrated that the administration of fecal samples rich in these enzymatic activities to mice did not correlate with an increase in tumorogenesis, suggesting that the function of these enzymes could be a way of reactivating estrogens that can be further metabolized in different ways (e.g., hydrolyzed, epimerized, oxidized, methylated) in distal sites. In parallel, Beck et al [ 75 ] demonstrated that treatment with β-glucuronidase inhibitors did not prevent breast cancer in mice.…”
Section: Discussionmentioning
confidence: 99%